2023
DOI: 10.3390/su15054530
|View full text |Cite
|
Sign up to set email alerts
|

Internal Branding in Hotels: Interaction Effects of Employee Engagement, Workplace Friendship, and Organizational Citizenship Behavior

Abstract: This study aimed to investigate three variables that may interact with internal branding (IB) in the hotel context: employee engagement (EE), workplace friendship (WF), and organizational citizenship behavior (OCB). This study adopted a survey methodology. 385 valid responses were collected from employees of 20 five-star chain hotels located in the Greater Cairo region of Egypt. The data were analyzed using PLS-SEM. The results demonstrated that there is a significant relationship between OCB and WF with EE, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Further, employees who have close ties with their coworkers have easier communication, trust, and collaboration. Having coworkers who are friends enhances the chance of cooperation, information sharing, and cohesive teamwork, resulting in higher levels of workplace engagement, as individuals feel a feeling of unity and a shared purpose [83,85] Furthermore, the findings revealed that psychological safety and workplace friendship mediate the relationship between benevolent leadership and job engagement, which is consistent with earlier research [9,82,93,97,103,104]. Benevolent leadership contributes to psychological safety, which allows employees to express their unique perspectives and ideas, resulting in increased job engagement and motivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, employees who have close ties with their coworkers have easier communication, trust, and collaboration. Having coworkers who are friends enhances the chance of cooperation, information sharing, and cohesive teamwork, resulting in higher levels of workplace engagement, as individuals feel a feeling of unity and a shared purpose [83,85] Furthermore, the findings revealed that psychological safety and workplace friendship mediate the relationship between benevolent leadership and job engagement, which is consistent with earlier research [9,82,93,97,103,104]. Benevolent leadership contributes to psychological safety, which allows employees to express their unique perspectives and ideas, resulting in increased job engagement and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…When employees have close relationships with their colleagues, it facilitates effective communication, trust, and cooperation. Having friends at work increases the likelihood of collaboration, knowledge sharing, and cohesive teamwork, resulting in elevated levels of job engagement as individuals experience a sense of unity and a shared purpose [83][84][85]. Additionally, the prevalence of workplace friendships contributes to a positive work environment.…”
Section: Relationship Between Workplace Friendship Prevalence and Job...mentioning
confidence: 99%
“…Within the population of interest, data were collected from subordinates who are close coworkers at family-style restaurants in Egypt using a simple random sampling approach. Greater Cairo was chosen because it is home to 40% of Egyptian residents (Khairy et al , 2023) and has expected visitors from other domestic cities and tourist-exporting countries (Khan et al , 2023b). Besides, Greater Cairo is characterized by famous tourist attractions such as the pyramids, the Sphinx and the Cairo Tower (Hemeda and Sonbol, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…By bridging these gaps, researchers can provide evidence-based recommendations to organizations in this industry, enabling them to foster supportive work environments that mitigate workplace negative gossip and organizational cynicism and reduce levels of work disengagement. The problem raised by the current study is even more of a concern in the tourism and hospitality industries, which are labor-intensive and employ a large number of people while also heavily depending on natural resources [20,21]. The tourism and hospitality business is also known for its fastpaced and dynamic nature, which requires staff to overcome a variety of challenges while providing great customer service [22].…”
Section: Introductionmentioning
confidence: 93%